Hallmarks of aging: middle-aging hypovascularity, tissue perfusion and nitric oxide perspective on healthspan - Teow J. Phua (Frontiers in Aging)
Aging is a complex process marked by various changes at both cellular and systemic levels, impacting the functioning and lifespan of organisms. Over time, researchers have pinpointed several significant hallmarks of aging that lead to the gradual deterioration of tissue function, regulation, and homeostasis associated with aging in humans. Despite this, the intricate interactions and cumulative effects of these hallmarks are still mostly uncharted territory. Understanding this complex web is a major challenge in Geroscience, yet it is crucial for developing effective strategies that promote healthy aging, reduce medical costs, and ensure the sustainability of health systems. Gaining insights in this area is essential for creating interventions that can slow the aging process, enhance healthspan, and decrease the likelihood of age-related diseases. The integration of knowledge from various fields concerning the middle-aging nitric oxide (NO)-mediated hypovascularity hypoxia hemodynamic hypothesis points to a systems-based approach to the biological hallmarks of aging. Key evidence suggests a systemic connection between the endocrine system (specifically sex hormones), endogenous NO deficiency, and the vascular system, which serves as a network of microvascular structures crucial for tissue perfusion functions at cellular level. These processes also involve oxidative stress and inflammation triggered by hypoxia.